Current perspectives in Sudanese and Nubian archaeology : a collection of papers presented at the 2018 Sudan Studies Research Conference, Cambridge - Lemos, Rennan; Tipper, Samantha (Access archaeology., 2021)
This book brings together papers presented at the 2nd Sudan Studies Research Conference, held at the McDonald Institute for Archaeological Research, University of Cambridge, 2018. The papers collected here focus on early administrative and mortuary material culture in the Nile valley and adjacent areas.